REKONDISI KELISTRIKAN ENGINE SUZUKI F8A - , M. SURYANDI PUTRA; , Ir. Susanto Johanes, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Internal combustion engine result in energy by burning the air and fuel mixture in the cylinder. The gasoline engine, the spark jumps the spark plug is needed to ignite the air-fuel mixture that has been compressed by the piston in the cylinder. While the diesel engine air is compressed by the high pressure so that it becomes very hot, and when fuel is sprayed into the cylinder, will be burned simultaneously. Because the gasoline engine combustion process initiated by a high voltage spark jumps generated by the spark plug, some method is needed to generate high voltage in need. Ignition system in the automobile serves to raise the voltage from the battery up to 10 kV or more by using the ignition coil and then distribute the high voltage to each spark plug via the distributor and high voltage cables. This battery type ignition system used on all gasoline engine for modern cars.